Impact and strategies of IoT facility management - Jaya Devi, Anathan; Liyana, Mohamed Yusof; Abdul Rahimi, Abdul Rahman (Construction Industry Development Board (CIDB), 2023)
A technological revolution is sweeping through the building industry, touching both government institutions and the private sector. The star of the show? The Internet of Things (IoT) is a transformative trend that's shaking up the very foundations of how we manage buildings. It is more than just a fad – it is a pivotal moment in reshaping the operational landscape of structures, and it is all thanks to the ingenious integration of IoT components by Facility Management (FM).